Development of palm fatty acid distillate-containing medium for biosurfactant production by Pseudomonas sp. LM19 - Abdul Hamid, Nurfarahin; Mohamed, Mohd Shamzi; Phang, Lai Yee (MDPI, 2019)
High production costs of biosurfactants are mainly caused by the usage of the expensive substrate and long fermentation period which undermines their potential in bioremediation processes, food, and cosmetic industries even though they, owing to the biodegradability, lower toxicity, and raise specificity traits. One way to circumvent this is to improvise the formulation of biosurfactant-production medium by using cheaper substrate. A culture medium utilizing palm fatty acid distillate (PFAD), a palm oil refinery by-product, was first developed through one-factor-at-a-time (OFAT) technique and further refined by means of the statistical design method of factorial and response surface modeling to enhance the biosurfactant production from Pseudomonas sp. LM19. The results shows that, the optimized culture medium containing: 1.148% (v/v) PFAD; 4.054 g/L KH2PO4; 1.30 g/L yeast extract; 0.023 g/L sodium-EDTA; 1.057 g/L MgSO4·7H2O; 0.75 g/L K2HPO4; 0.20 g/L CaCl2·2H2O; 0.080 g/L FeCl3·6H2O gave the maximum biosurfactant productivity. This study demonstrated that the cell concentration and biosurfactant productivity could reach up to 8.5 × 109 CFU/mL and 0.346 g/L/day, respectively after seven days of growth, which were comparable to the values predicted by an RSM regression model, i.e., 8.4 × 109 CFU/mL and 0.347 g/L/day, respectively. Eleven rhamnolipid congeners were detected, in which dirhamnolipid accounted for 58% and monorhamnolipid was 42%. All in all, manipulation of palm oil by-products proved to be a feasible substrate for increasing the biosurfactant production about 3.55-fold as shown in this study.